2020
DOI: 10.3390/agronomy10040568
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Efficiency and Influencing Factors of New Soybean Producing Farms

Abstract: The efficiency of new soybean producers is of great importance to the agricultural development of China. Based on the survey data of some counties (cities) in Heilongjiang, Jilin, Liaoning, and Inner Mongolia Autonomous Region, the efficiency of new soybean producers in these regions is calculated by means of the data envelopment analysis (DEA) model. Then, the Tobit model is used to select relevant explanatory variables to study the factors affecting the production efficiency, and relevant conclusions and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…There are no farmers in the seriously lowefficiency category (TE<0.4), while there are only 7.50% farmers in the Efficiency category (0.99 ≤ TE). These results are in line with research by [25], which showed that the most soybean farmers in Heilongjiang Province, Jilin Province, Liaoning Province, and Inner Mongolia Autonomous Region were in the moderately low-efficiency and slightly low-efficiency categories. The technical efficiency of the Biosoy variety is in the slightly low efficiency and efficiency categories, and this shows that the level of technical efficiency is higher than the Anjasmoro variety.…”
Section: Technical Efficiency Of Early-maturity Soybean Varietiessupporting
confidence: 91%
See 1 more Smart Citation
“…There are no farmers in the seriously lowefficiency category (TE<0.4), while there are only 7.50% farmers in the Efficiency category (0.99 ≤ TE). These results are in line with research by [25], which showed that the most soybean farmers in Heilongjiang Province, Jilin Province, Liaoning Province, and Inner Mongolia Autonomous Region were in the moderately low-efficiency and slightly low-efficiency categories. The technical efficiency of the Biosoy variety is in the slightly low efficiency and efficiency categories, and this shows that the level of technical efficiency is higher than the Anjasmoro variety.…”
Section: Technical Efficiency Of Early-maturity Soybean Varietiessupporting
confidence: 91%
“…If TEi approaches 1, farming becomes increasingly efficient. If TEi approaches 0, it indicates decreasing technical Efficiency.Technical efficiency levels are categorized into four classes: seriously low Efficiency (TE < 0.4), moderately low Efficiency (0.4 ≤ TE < 0.7), slightly low Efficiency (0.7 ≤ TE < 0.99), and Efficiency (0.99 ≤ TE)[25].…”
mentioning
confidence: 99%
“…Extensive research has been conducted on the total factor productivity and the impact of inputs on output [30][31][32][33][34]. The total factor productivity of dairy farming has been measured recently [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the characteristics of agricultural development and the current production situation, in order to prevent errors in omitted variables, this paper selects the following five control variables. Education level (Edu): the increase in the education level of farmers is conducive to the optimal allocation of agricultural production resources and technical efficiency 46 . At the same time, agricultural production relies more on the improvement of labor quality and technological progress, thus driving agricultural green production and changing the crude production method to improve the AGTFP.…”
Section: Variable Selection and Data Resourcementioning
confidence: 99%
“…Education level (Edu): the increase in the education level of farmers is conducive to the optimal allocation of agricultural production resources and technical efficiency 46 . At the same time, agricultural production relies more on the improvement of labor quality and technological progress, thus driving agricultural green production and changing the crude production method to improve the AGTFP.…”
Section: Variable Selection and Data Resourcementioning
confidence: 99%